Effect of Fertilizer Types and Plant Densities on Oil Components of Milk Thistle (Silybum marianum L.) Under Rainfed and Irrigated Conditions - Ahmed, Rozhgar Mustafa; Askari2, Ali Abdulrahman; Baban, Shirwan Omer (Sulaimani Journal for Pure and Applied Sciences, 2018)
The present study was conducted at Bazian location during two winter seasons of 2010- 2011 and 2011- 2012 A factorial experiment was conducted using Completely Randomized Block Design (CRBD) with three replications. The study included two different irrigation; Rainfed and Irrigated, combined with three fertilization applications; No fertilization Chemical fertilization and Organic fertilization and two different plant densities; 8and 16 plant m-2. The most important results of the average of both seasons can be summarized as follows:- Seed samples were analyzed quantitatively by HPLC for their content of unsaturated fatty acids; α-Linolenic, Linoleic, Oleic and Gadoleic acid. Data showed that effect of irrigation treatment was significant in the amount of Linoleic and Oleic acids, while Gadoleic showed significant differences due to no fertilizer treatment. α-Linolenic respond significantly to the interaction between chemical fertilizer and 8 plant m-2.
Keywords: Medicinal Plant; Milk thistle; Fertilization; Irrigation; Plant density; Unsaturated fatty acids